Mechanical behavior of unidirectional composites according different failure criteria - Adel Deliou; Benattou Bouchouicha (Fracture and Structural Integrity)
This work is about study of the mechanical behaviour of unidirectional Kevlar / Epoxy composite laminates according to different failure criteria. Varying strength parameters values, makes it possible to compare the ultimate mechanical characteristics obtained by the criteria of Tsai-Hill, Norris, Fisher, Ashkenazi and Tsai-Wu. The epoxy matrix of the material in question is reinforced with up to 60% of its volume by aramid fibers. The stack of four layers composing the arbitrarily oriented and alternating [+?/-?]S materials results in balanced symmetrical laminates. The laminate is subjected to uniaxial tensile membrane forces. Estimate of their ultimate strengths and the plotting of the failure envelope constitute the principal axis of this study. Using the theory of maximum stress, we can determine the various modes of damage of the composite. The different components of the deformation are presented for different orientations of fibers.